Analysis of anti-rheumatic activity of Nyctanthes arbor-tristis via in vivo and pharmacovigilance approaches - Sharma, Ayushi; Goel, Anjana; Lin, Zhijian (Frontiers in Pharmacology, 2023)
Introduction-Rheumatoid arthritis (RA) is an immune-mediated disease associated with chronic inflammation of numerous joints. Nyctanthes arbour-tristis (NAT) is a traditional remedy for rheumatoid arthritis, a chronic inflammatory disorder.Aim-The current project was intended to demonstrate the role in the sub-acute toxicity, pharmacovigilance and anti-rheumatic biomarkers of the NAT extracts.Method-Hydroethanolic extract (1:1) of the plant leaves was prepared by reflux method. The safe dose was evaluated in Sprague-Dawley rats and the anti-inflammatory effects of NAT on rheumatoid arthritis symptoms including, paw volumes, body weight, arthritic index, withdrawal latency, hematology and serological test, radiology, and histopathology were evaluated in complete Freund's adjuvant-induced arthritis Sprague-Dawley rat models. The inflammatory (TNF-α and COX-2), as well as anti-inflammatory markers (IL-10), were analyzed in control and experimental groups.Result-The study showed that 500 mg/kg B.W NAT leaf extract was found to be maximum nontoxic without showing ant subacute toxicity symptoms. In pharmacovigilance study highlighted potential side effects of NAT, such as drowsiness, sedation, and lethargy at high dosages. Plant extract mitigated the paw edema, restored the immune organ and body weights, and ameliorated the level of blood parameters such as hemoglobin, red blood cells, platelets, white blood cells, aspartate aminotransferase This is a provisional file, not the final typeset article (AST), Alanine transaminase (ALT), C-reactive proteins, and rheumatoid factor. Treatment with the plant extracts also reduced the level of Cyclooxygenase 2 and TNF-α and increased the level of IL-10 in the serum of arthritic rats dose-dependently. Radiographic analysis of the ankle joint showed the improvement in the hind legs. Histological examination of ankle joints revealed that the plant extracts decreased the pannus formation, inflammation, and synovial hyperplasia in arthritic animals.Conclusion-NAT 500 mg/kg could serve as a promising therapeutic option for the treatment of inflammatory arthritis.